Classical open aorto-bi-femoral grafting is a gold standard technique in aorto-iliac occlusive disease: The technique of double layered reinforcing aorto-graft proximal anastomosis with anterior augmentation patchplasty and its advantages. Issue 2 (2018) - Haridas, Arun Kumar; Bhat, Bharathi Shridhar
No abstract available